(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The study Aims to reveal the changes of vegetation cover in DhiQar Governorate, southern Iraq for the period (1990-2022) by using the Landsat satellite visualizations, as the spectral data of four satellite visualizations for the years 1990, 2000, 2010, 2010 and 2022 were analyzed and digital processing was performed on them in the Erdas Imagine 2014 program. And exporting it to the Arc GIS 10.5 program to study the spectral indicators of vegetation cover, as the Normalized Differtation Index (NDVI) was adopted to monitor the time sequence of the change in the vegetation area in the study area, as the research concluded that the vegetation cover in the year 1990 was in a very good condition, as it occupied 4721 km 2 and 34.1% of the total area of the study area of 13812 km 2, while the vegetation cover decreased in the year 2000 to cover 10.8% of the study area, and in the year 2010 the percentage of vegetation coverage reached 20.6%, but in the year 2022 the area of vegetation decreased significantly as It does not exceed 932 km 2 and is only 6.7% of the total area of the study area, recording a large change rate of 80% over the year 1990, which indicates land degradation and a decline in areas suitable for To cultivate and aggravate the problem of desertification resulting from climatic changes on the one hand and the significant decrease in the water revenue of the rivers of the study area on the other hand